Antiquity: a View from Modernity (“Medea” in Teatr na Taganke and in Moscow Teatr Yunogo Zritelya) - Шелогурова, Галина Н. (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
Comparing the two interpretations of Medeas’s myth the author of the article is primarily interested in the problem of the perspectives of genre (tragedy as it was defined by Aristotle) in modern theatre. In this connection the most important aspect of the analysis is the esthetic, philosophical and social bases of tragedy. That is why Lubimov’s stage variant of the ancient myth seems to be the presentation of the specific moment – the maximal rapprochement between classical tragedy and Russian life of the 1990s. Medea staged 14 years later by Ginkas fixed the situation when such a contact was appreciated as impossible.